THE RELATIONSHIP BETWEEN THE ATTITUDE OF LAW ENFORCEMENT OFFICERS AND CIVILIANS TO LIES WITH THE SUCCESS OF ITS RECOGNITION - Новицька, Ія В’ячеславівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
The article is devoted to the description of attitude to lies and success of its detection in groups of civil recipients and police. Results of two empirical studies are presented in the article. At the first study (n = 120) was found that civil recipients are better in deception detection if they have epistemological understanding of concept of lie. Those recipients who understand the lie from a moral position, condemn it – are worse in lie detection. Those recipients who considers the main motive of lies is «to create a good effect» are also successful in deception detection. Perhaps this motive is projection, and people who have this motive are more attentive to the communicant, spend more effort to recognize verbal and non-verbal cues. The comparison group of recipients who rely on scientifically confirmed and unconfirmed cues of deception was shown, that scientifically confirmed group is better in lie detection. In a group of civil recipients it was shown that attitudes to different types of lies are correlated. It was also found that the better a person evaluates himself as a successful liar, the more often he uses lie in life and the more positive attitude to lies. However, the attitude to different types of lies is not correlated with the success of detection lie, truth and messages (lie+rtuth) - only with self-esteem as a successful or unsuccessful recipient. In the second study (n = 62) it was found that lie detection in police is not correlated with age, work experience, attitude to white lies. The police, in general, are more aware of the cues of lie, more often civilians rely on scientifically confirmed, in particular, verbal cues. However focus on scientifically confirmed cues of lie is associated with prejudgment in police. The main motive of lies «to create a good effect» named by the police improves lie detection, like in civil group. But understanding lie as ontological or moral position is not associated with lie detection in police. In general, both groups detect lies at the level of random guessing (50%), which is consistent with other studies. Differences in success in detection of messages (lie+rtuth) are due to bias. Biases, probably, are more associated with attitude to lie.